Vocational training and gender: wages and occupational mobility among young workers - Bernd Fitzenberger; Astrid Kunze (Institute for the Study of Labor (IZA), 2005)
This paper investigates the relationship between the gender wage gap, the choice of training occupation, and occupational mobility. We use longitudinal data for young workers with apprenticeship training in West Germany. Workers make occupational career choices early during their careers and women and men pursue very different occupational careers. We reconsider whether through occupational segregation women are locked in low wage careers (Kunze, 2005) or whether they can move up to higher wage paths through mobility. We furthermore investigate whether patterns have changed across cohorts during the period 1975 and 2001 and whether effects vary across the distribution. The main results are: First, while there exists a persistent gender wage gap over experience, the gap has decreased over time. Second, in the lower part of the wage distribution, the gap is highest and it increases with experience. Third, occupational mobility is lower for women than for men and the wage gains due to occupational mobility are higher for men than for women, especially in the lower part of the wage distribution. We conclude that occupational mobility has reduced the gender wage gap, but lock-in effects are still stronger for women compared to men.
Keywords: C21; J16; J24; J31; J62; J7; 330; gender wage gap; actual experience; occupational mobility; apprenticeship; Betriebliche Berufsausbildung; Arbeitsmobilität; Lohndifferenzierung; Schätzung; Deutschland; Geschlechterdiskriminierung